A comparative study on water deficit stress tolerance between the cowpea (Vigna Unguiculata [L.] walp) and soybean (Glycine max [L.] merrill) - Lutombo, Mulalo (My University, 2023)
The world has lately suffered prominent natural disasters, most with potential to extirpate all form of life. Drought comes in second to hurricanes in regards to causing severe economic impacts worldwide. Drought is a prolonged period of not enough rainfall or below average precipitation that results in shortage of water in the soil. Water shortage crisis and its effects can be easily observed in the agricultural sector. Each year, the agricultural sector and the food supply chains suffer a loss worth R100s trillions of the total average yield of agro-economic crop due to drought stress. Soybean production in sub-Saharan Africa is still low as is anywhere in Africa. The production could be much higher but local farmers suffer harsh environmental conditions such as pest, diseases and drought. Conventionally cowpea is considered the trunnion of small farmers in Central and West African regions. This is because it is well adapted to areas with lower rainfall. The aim of this study was to investigate the similarities and dissimilarities between soybean and cowpea’s response and tolerance to water deficit stress. Three genotypes where used for each plant, Red, Blonde and white (cowpea) and TGx 1937-f, PAN 1664R and LS 678 (soybean). Polyethylene glycerol 8000 was used to induce drought stress at five different levels of osmotic potential (of 0.00, -0.02, -0.27, -1.27, and -1.80 MPa) for evaluation of water deficit tolerance during germination. To assess both vegetative and reproductive growth plants were subjected to three drought stress levels; control- watered daily (no water stress), moderate (watered once in 5 days) and severe (watered once in seven days). Morphological parameters (number leaves, length of stem, root length, mass of the nodules, number of flowers, number of pods, seeds per pod, mean seed number per pod and mass of 100 seeds) were directly counted or measured on the plants. Samples were collected for physiological analyses including determination of proline content, determination of leaf relative water content, determination of malondialdyde content and determination of chlorophyll content. Lastly, an experiment to assess the ability of cowpea and soybean to recover from. Plants were subjected to drought for 14 days followed by re-watering for two weeks and the samples were collected for physiological analyses mentioned above. The control set was watered daily. The results showed that the seed germination percentage and mean daily germination declined with the increase in water stress severity reaching lower than 10% germination at the lowest osmotic potential treatment (-1.80 MPa) for both cowpea and soybean. Germination results showed no significant differences between cowpea and soybean for all parameter. However, cowpea was significantly different from soybean with regard to vi seedling growth parameters. Morphological results showed that soybean nodule weight significantly decreased as the stress severity increased. Cowpea nodule weight, number of stomata on both surfaces, and root length showed no significant difference between treatments and also between the genotypes. White genotype cowpea had a significantly lower root length and nodule weight and a slightly lower number of stomata but not significantly different from the other genotypes. Drought stress decreased the leaf relative water content of both cowpea and soybean under moderate and severe stress. However, cowpea performed distinctly superior to soybean. Cowpea with its lower nodule weight maintained no significant difference between all treatments. Water deficit stress affected leaf development. The highest number of leaves 1st count were 24.60 and 16.50 (control) and the lowest count was 19.33 and 14.50 (severe) for cowpea and soybean, respectively. The 1st count of the number of leaves of soybean genotypes showed a significant difference between genotypes for all water stress treatments with the exception of TGx 1937-f and PAN 1664R under severe stress, 20.16 and 20.83, respectively. With regards to water stress metabolites, the proline content and malondialdehyde content of both beans were significantly increased comparing control with stressed treatments. However, malondialdehyde content and proline content of soybean was significantly higher than cowpea for both control and stressed plants. The same trend was observed for stressed-rewatered experiment. The recovery response of cowpea was excellent and better than soybean which failed to recover. Considering morphological and physiological parameter during vegetative growth, the results suggested that cowpea response better to water stress than soybean. In conclusion, cowpea response and tolerate water deficit stress better than soybean. In future, it is necessary to genetically compare the two legume plants, to trace the genes that are responsible for such tolerance in cowpea.
Thesis (M.Sc. (Botany))-- University of Limpopo, 2023
Keywords: Cowpea; Soybean; Water deficit stress; Drought; Crops -- Drought tolerance; Droughts; Cowpea; Soybean